Entering the Conversation: Introduction to the Special Issue - Paré, David; Thériault, Anne (Canadian Journal of Counselling and Psychotherapy, 2010)
The introduction to the special issue on counsellor supervision lays out the context that gave rise to this project: a two-day funded workshop that gathered researchers and practitioners of supervision from across Canada as well as two prominent academics from the United States. Highlights of the conference are discussed as well as implications for supervision in Canada.